2016
DOI: 10.1016/j.joms.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Does Length, Diameter, or Bone Quality Affect Primary and Secondary Stability in Self-Tapping Dental Implants?

Abstract: IT and primary ISQ in self-tapping implants differed in patients with different bone quality and implant diameter but did not differ between the 2 implant lengths compared in this study. Secondary stability was not substantially affected by any of these factors. Although IT was closely related to primary ISQ, it was unrelated to secondary ISQ. Very high primary ISQ values tended to decrease, whereas intermediate and low values tended to increase, in the transition to secondary stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
48
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 26 publications
9
48
3
1
Order By: Relevance
“…Similar findings were reported in a human cadaver maxilla model evaluating the primary stability of variable‐thread tapered implants of different diameters . The lack of statistically significant differences in ITVs between different implant lengths is in line with the clinical findings of Gómez‐Polo et al . This can be justified by the fact that implant design may prevail over implant dimensions as a contributing factor in primary stability in some implant systems.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar findings were reported in a human cadaver maxilla model evaluating the primary stability of variable‐thread tapered implants of different diameters . The lack of statistically significant differences in ITVs between different implant lengths is in line with the clinical findings of Gómez‐Polo et al . This can be justified by the fact that implant design may prevail over implant dimensions as a contributing factor in primary stability in some implant systems.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, there is a lack of consensus relative to the impact of implant length on ITVs. Implant length seems to be critical in obtaining higher primary stabiltiy in some studies, while others reported no influence of implant length on ITVs . The impact of implant diameter and length on primary stability was not evident in this study, as ITVs did not significantly differ between various implant diameters and lengths in all three bone qualities taken jointly or in D4 bone considered separately.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Experimental results by Soskolne et al (Soskolne et al 2002) showed an increased adherence of monocytes to titanium disks with moderately rough surfaces as compared to plastic surfaces. A recent longitudinal clinical study demonstrated that implant length was not associated with the primary and secondary stability of self-tapping dental implants (Gomez-Polo et al 2016). Although bone quality and PS at the time of implant insertion remained uninvestigated in the present study, it is hypothesized that both groups exhibited a considerable amount of PS and favorable bone type.…”
Section: Discussionmentioning
confidence: 62%
“…A recent longitudinal clinical study demonstrated that implant length was not associated with the primary and secondary stability of self‐tapping dental implants (Gomez‐Polo et al. ). Although bone quality and PS at the time of implant insertion remained uninvestigated in the present study, it is hypothesized that both groups exhibited a considerable amount of PS and favorable bone type.…”
Section: Discussionmentioning
confidence: 99%